Polarization microwave correlation imaging method based on orthogonal complement space - Runkun Tian; Dahai Dai; Penghui Ji; Bo Pang; Shilong Sun (Electronics Letters, 2023)
Abstract Currently, microwave correlation imaging (MCI) is regarded as an important method to address the forward‐looking imaging problem in radar. The key step of this method is to form a spatio‐temporal two‐dimensional random radiation field through various means. However, the current methods do not consider the polarization domain, which is an important dimension of electromagnetic signals. The existing research mainly focuses on using polarized antenna elements, without incorporating polarization information into the imaging system. To fill this gap, this letter proposes the polarization microwave correlation imaging (PMCI) based on the orthogonal complement space, which performs instantaneous polarization measurements (IPM) while correlating imaging of the target. Through simulation analysis, this method can further improve the quality and anti‐interference ability of MCI. Moreover, under the condition of low time‐frequency product, the peak sidelobe level (PSL) and isolation of this method are approximately 3.5 dB and 12.5 dB higher than those of traditional instantaneous polarization measurement methods (TIPM).